Scaling technology ventures in Africa: new opportunities for research. Issue 4 (2nd October 2022) - Weiss, Tim; Perkmann, Markus; Phillips, Nelson
ABSTRACT: Research on new venture creation in Africa is growing rapidly. This increasing interest reflects both the potential for entrepreneurship to contribute to the economic and social development of Africa, as well as the potential for this research to provide new insights that challenge and extend theories developed primarily from studies of North American and European new ventures. In this editorial essay, we argue for an expansion of this important research stream to include a focus on how technology ventures scale in Africa. We identify seven topics that offer interesting opportunities for research on scaling in Africa: (1) the effect of venture location on scaling; (2) the effect of founding team diversity on scaling; (3) the effect of entrepreneurial strategies on scaling; (4) the effect of nascent ecosystems on scaling; (5) the effect of the institutional environment on scaling; (6) the effect of nascent financial markets on scaling; and (7) the societal effects of scaling. We discuss each of these topics, their potential to contribute to the existing literature, and provide examples of African technology firms that have scaled to illustrate each topic. We conclude with a discussion of how African social, political, and regulatory change, combined with rapidly developing entrepreneurial ecosystems, are creating a context where the successful scaling of technology ventures is becoming increasingly common, and research is therefore increasingly valuable.